2018
DOI: 10.1111/birt.12355
|View full text |Cite
|
Sign up to set email alerts
|

The impact of epidural analgesia on the duration of the second stage of labor

Abstract: Our findings suggest a significant prolongation of the second stage in women receiving epidural analgesia. Recommendations for management of second stage should be reconsidered by contemporary data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 27 publications
3
27
0
2
Order By: Relevance
“…Oxytocin administration was also associated with decreased rate of normal vaginal delivery; in a previous study only 51.1% of parturients who received augmentation with oxytocin achieved a normal vaginal delivery compared with 76.5% of parturients who did not need augmentation (RR 0.67; CI 0.63‐0.71) 14 . Nulliparity has been shown to be a risk factor for an increased length of second stage of labor 15 . A recent study showed that a BMI of ≥‐30 increased risk of an intrapartum cesarean delivery by 77% 16 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Oxytocin administration was also associated with decreased rate of normal vaginal delivery; in a previous study only 51.1% of parturients who received augmentation with oxytocin achieved a normal vaginal delivery compared with 76.5% of parturients who did not need augmentation (RR 0.67; CI 0.63‐0.71) 14 . Nulliparity has been shown to be a risk factor for an increased length of second stage of labor 15 . A recent study showed that a BMI of ≥‐30 increased risk of an intrapartum cesarean delivery by 77% 16 …”
Section: Discussionmentioning
confidence: 97%
“…Risk factors for having an operative delivery included: ECR, nulliparity, oxytocin, male neonatal sex, and maternal BMI > 35 kg/m 2 . These factors have been shown in previous studies to decrease the rate of normal vaginal delivery 13‐15 . Risk factors for ECR analysis included: BMI ≥ 35 kg/m 2 , nulliparity, cervical opening ≥ 3 cm, male neonatal sex, fetal weight > 3.5 kg and catheter depth over 5 cm.…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence that epidural analgesia will lengthen the second stage of labour. Shmueli et al 1 retrospectively demonstrated that the use of epidural analgesia extended the second stage of labour by 95 min (193 vs 98 min of the 95th percentile for epidural vs no epidural, respectively). Cheng et al 2 found that epidural analgesia was associated with more than a 2-hour (the difference of the 95th percentile threshold) prolongation of the second stage of labour for both nulliparous and multiparous women.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the clear benefit of pain reduction, management measures should not interfere with the normal birth process. The literature has become increasingly focused on the maternal and fetal effects of intrapartum analgesia 5 , 6 , 7 , although little is known still about the use of i. v. PCA with remifentanil in a German population 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Trotz des klaren Nutzens der Schmerzreduktion sollten steuernde Maßnahmen den physiologischen Ablauf der Geburt nicht beeinträchtigen. Die Literatur hat sich mit den maternalen und fetalen Auswirkungen der intrapartalen Analgesie zunehmend beschäftigt 5 , 6 , 7 , wobei zum Einsatz der i. v. PCA mit Remifentanil in einem deutschen Kollektiv bisher noch wenig bekannt ist 8 .…”
Section: Introductionunclassified